Evaluasi Program Gala Desa Tahun 2017 di Kementerian Pemuda dan Olahraga - Yagusta, Rani Aggra Berta; Widiastuti, Widiastuti; Puspitorini, Wahyuningtyas; Pradityana, Karisdha (UIR Press, 2019)
This study aimed to describe and evaluate Gala Desa Program 2017 which was organized by Ministry of Youth and Sports ministry and synergized with Ministry of Village, Underdeveloped Regions Development, and Transmigration. There were sixth competitions provided namely Badminton, Football, Volleyball, Sepak Takraw, Table Tennis and Athletic. This program was held in 34 provinces, 136 regions/cities, 816 villages (one village held one sport branch). This study was qualitative approach by using four research instruments to convey the data such as interview, observation, documentation, and FGD. There were 361 respondents involved in this study. To analyze the data, researchers used CIPP (context, input, process, product) method which developed by Daniel L. Stufflebeam et al. Based on the data conveyed, the result showed that; 1) context component which involved low and government policy, intention and objective, and then target of Gala Desa program 2017 was good  category (45%), 2) Input component, which involved participants, organizer, financing, and committee showed that the result was good category (37%). 3) process component which involved rules of competition and implementation of Gala Desa program 2017 was categorized as good (41%). 4) Product Evaluation component which involved level of participation and public interest, and the role of media in publication and promotion of playing sports to society was categorized as very good (57%). This program that was created by the Ministry of Youth and Sports was effective to monitor and measure the successful of government program to encourage people to love doing sports.